Proceso de Selección de personal del Gobierno Autónomo Descentralizado Municipal del Cantón Babahoyo - Cerezo Pacheco, Maoly Michelle (2019)
The Municipal Autonomous Decentralized Government of Babahoyo Canton, is located on General Barona Avenue between Calderón and May 27, began work on May 27, 1869. It is in the mandate of Eng. Guido Silva, who will be responsible for making meet the objectives proposed in its period 2018 - 2019. The municipality of the Babahoyo canton, is a public company with administrative, financial and political autonomy, its objective is to meet the requirements and needs of Babahoyo canton, effectively, efficiently and with quality